2022
DOI: 10.3390/nu14051080
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Postprandial Walking on the Glucose Response after Meals with Different Characteristics

Abstract: We evaluated the effect of postprandial walking on the post-meal glycemic response after meals with different characteristics. Twenty-one healthy young volunteers participated in one of two randomized repeated measures studies. Study 1 (10 participants) assessed the effects of 30 min of brisk walking after meals with different carbohydrate (CHO) content (0.75 or 1.5 g of CHO per kg/body weight). Study 2 (11 participants) evaluated the effects of 30 min of brisk walking after consuming a mixed meal or a CHO dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…Exercise is a valuable tool for improving the acute glycemic response to a meal in healthy and diabetic individuals. Several studies have suggested that exercise-induced reductions in postprandial glycemia have important effects on the cardiometabolic state of individuals [1][2][3][4][5][6][7][8]. The effect of exercise on the glycemic response may change considerably depending on when an exercise session is performed with respect to the meal.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exercise is a valuable tool for improving the acute glycemic response to a meal in healthy and diabetic individuals. Several studies have suggested that exercise-induced reductions in postprandial glycemia have important effects on the cardiometabolic state of individuals [1][2][3][4][5][6][7][8]. The effect of exercise on the glycemic response may change considerably depending on when an exercise session is performed with respect to the meal.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, different exercise types (e.g., running, walking, cycling, resistance exercise and different combinations of resistance and aerobic exercise) are similarly effective in reducing the postprandial glucose response [2,4,5], with only minor between-type differences observed in most of the cases. Therefore, it has been suggested that 30 min of brisk walking is a valid exercise strategy for different populations [2,3]. However, the fact that different postprandial exercise types 2 of 15 have similar effects on the glycemic response has other implications that require further consideration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Friend and Stranger Conditions, unlike the Alone Condition, energy consumption occurred during skeletal muscle movement associated with speech, and it is possible that this may have affected blood sugar level fluctuations. However, when energy is consumed by skeletal muscles during exercise such as walking immediately after a glucose load, blood glucose levels drop significantly immediately afterward [34]. In this study, although the amount of speech during communication was the same as that shown in Figure 3, the blood sugar level at 15 min did not differ significantly between the three conditions, as shown in Figure 5b.…”
Section: Discussionmentioning
confidence: 44%
“…Conversely, the latter model embraces interdependency between dietary and exercise responses in a synergistic manner. This is substantiated by contemporary medical insights that highlight how the impact of postprandial exercise on glucose reduction is contingent upon carbohydrate intake levels [26] and the elevation in postprandial blood glucose [27]. Our supposition in the synergistic model postulates that such interactive impacts manifest through the multiplication of dietary and exercise effects.…”
Section: Methodsmentioning
confidence: 88%